2006
DOI: 10.1158/0008-5472.can-06-0283
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Implications of a Human Neutralizing Antibody to the Macrophage-Stimulating Protein Receptor Tyrosine Kinase (RON), a c-MET Family Member

Abstract: RON is a member of the c-MET receptor tyrosine kinase family. Like c-MET, RON is expressed by a variety of epithelial-derived tumors and cancer cell lines and it is thought to play a functional role in tumorigenesis. To date, antagonists of RON activity have not been tested in vivo to validate RON as a potential cancer target. In this report, we used an antibody phage display library to generate IMC-41A10, a human immunoglobulin G1 (IgG1) antibody that binds with high affinity (ED 50 = 0.15 nmol/L) to RON and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
137
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(145 citation statements)
references
References 45 publications
8
137
0
Order By: Relevance
“…Various studies have shown that therapeutic antibodies and TKIs specific to RON inhibit tumor growth mediated by pancreatic, colon, and breast cancer cells in mouse tumor xenograft models (7,12,13,31). Studies using BMS-777607 to target MET have shown the effectiveness in inhibiting MET-mediated tumor cell migration, matrix invasion, and distance metastasis (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies have shown that therapeutic antibodies and TKIs specific to RON inhibit tumor growth mediated by pancreatic, colon, and breast cancer cells in mouse tumor xenograft models (7,12,13,31). Studies using BMS-777607 to target MET have shown the effectiveness in inhibiting MET-mediated tumor cell migration, matrix invasion, and distance metastasis (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant RON expression also has been molecularly targeted in mouse xenograph models of pancreatic ductal adenocarcinoma (PDAC; refs. [5][6][7]. PDAC is a highly malignant disease with limited treatment options (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects were found to be dependent on hypoxic RON expression further strengthening the utility of targeting RON signaling pathway in CRC. Another RON binding antibody IMC41A10 developed by ImClone Systems has been shown to block the interaction between RON and its ligand MSP with a high affinity [63]. The efficacy of RON kinase has been demonstrated in several cancers including HT29 colon cancer cells wherein IMC41A10 has been shown to inhibit MSP induced phosphorylation and downstream signaling events.…”
Section: Ron Signaling In Crcmentioning
confidence: 99%